The Students and Teachers' Perspectives on Using Bima Language in Teaching English - Supriadin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This research investigates the students and teachers’ perspectives on using Bima language in teaching English. The data collected through video recorder, reflection, and interview. The data analysed using qualitative method such as identifying, classifying, explaining, and concluding. This research shows that; firstly, based on the video recorder, students looked anthusiast in taking part to the English class activities. They were active and cohesive in translating every untterance that mentioned by the English teacher in mother tongue. Secondly, the reflection shows that the students’ vocabulary and speaking can be improved. It is different with the previous one when the treatment has not been applied. Lastly, the interview result indicates that the students and teachers’ responses tend to give positive response on the application of Bima language in teaching English. It can be seen from the students’ responses percentage; 85% students gave most positive responses, 6% students gave semi-positive responses, 6% students gave semi-negative responses, and 3% students gave negative responses. On the other hand, the English teachers’ responses also reflect on positive, because after they observed the learning activities, they aware that the Bima language has big potensial to be used in teaching English. Interestingly, they saw their students’ English ability can be  improved after they learn it by using mother tongue. Therefore, it can be concluded that using Bima language can give positive contribution in teaching English.